The contribution of institutional factors to course satisfaction with perceived learning as a mediator among student in Malaysian research universities - Amoozegar, Azadeh; Mohd Daud, Shaffe; Mahmud, Rosnaini; Ab. Jalil, Habibah (Human Resource Management Academic Research Society, 2017)
Distance learning in Malaysia has seen phenomenal growth especially in higher education where there are numerous universities offering online courses that have specifically provided access to students who were challenged by space and time constraints. Regardless of the dramatic increase of online courses and student enrollment, there are many indications that online courses are unsuccessful at meeting students’ needs and students are dissatisfied with their online course experiences, which brings about a serious concern regarding the dropout rates of online courses. For solving this issue, it is crucial that researchers identify and study the factors that lead to student satisfaction with online courses because course satisfaction is considered to be the largest determinant in reducing dropout in distance learning environment. Hence, the purpose of this study is to investigate the contribution of institutional factors in terms of support including technical support, administrative support, and university support toward course satisfaction among 367 undergraduate distance students in Malaysian research universities. The result of the study revealed that institutional factors were a significantly positive, and strong factor associated with course satisfaction. Further, both direct and indirect effects of institutional factors on course satisfaction were significant, which means the effect of this variable on course satisfaction is partially mediated by perceived learning.